ANALISIS KARAKTERISTIK MATERIAL ELEKTRODA TIP UNTUK PROSES LAS TITIK PADA BODI MOBIL UNTUK RANGKA MEMPERPANJANG UMUR PAKAI - Effendi, Riki; Hendra, Franka (DINAMIS, 2022)
One of the important components in the process of spot welding or spot welding is electrode tip or better known asâ€eltip". The quality of eltip material will greatly determine the welding results, the level of reliability and service life of eltip. The purpose of this study was to analyze the characteristics of eltip and find a suitable formulation of locally produced eltip to replace imported eltip. The chemical composition of the eltip material that is currently used is unknown and is a secret for import manufacturers. Local production Eltip used spot welding process has a disadvantage in service life. For this reason, chemical composition tests, hardness tests, and metallographic tests were carried out on the tip electrode. In the results of spot welding metallographic test and tark test, the results showed a minimum nugget diameter of 3 mm for 1 mm thick welding plate, can be met between 3.22 mm to 3.52 mm by local eltip. The service life of local eltip as many as 2000 spots is approaching the service life of imported eltip as many as 2400 spots. A slight improvement in Pb levels as an anti-wear will increase the service life of this local eltip in subsequent use. With reference to the quality standards of the Weld, such as the dimensions of the nugget, and visual check welding surface defects allowed by the car manufacturer, the results of this study are expected to be a reference for the use of eltip in the welding process elsewhere.